Bone regeneration in dehiscence-type defects at chemically modified (SLActives) and conventional SLA titanium implants: a pilot study in dogs - Frank Schwarz, Monika Herten (Blackwell Synergy, 2007)
Objectives: The aim of the present study was to evaluate bone regeneration in dehiscence-type defects at titanium implants with chemically modified (mod) and conventional sand-blasted/acid-etched (SLA) surfaces. Material and Methods: Standardized buccal dehiscence defects (height: 3 mm, width: 3 mm) were surgically created following implant site preparation in both the upper and lower jaws of four beagle dogs. modSLA and SLA implants were inserted bilaterally according to a split-mouth design. The animals were sacrificed after 2 and 12 weeks (n52 animals each). Dissected blocks were processed for histomorphometrical analysis: defect length, new bone height (NBH), percent linear fill (PLF), percent of bone-to-implant contact (BIC-D) and area of new bone fill (BF). Results: Wound healing at SLA implants was predominantly characterized by the formation of a dense connective tissue at 2 and 12 weeks, without significant increases in mean NBH, PLF, BIC-D or BF values. In contrast, modSLA implants exhibited a complete defect fill at 12 weeks following implant placement. In particular, histomorphometrical analysis revealed the following mean values at 12 weeks: NBH (3.2 0.3 mm), PLF (98%), BIC-D (82%) and BF (2.3 0.4mm2). Conclusion: Within the limits of the present study, it was concluded that modSLA titanium surfaces may promote bone regeneration in acute-type buccal dehiscence defects at submerged implants.